Anopheles farauti is a homogeneous population that blood feeds early and outdoors in the Solomon Islands. (December 2016) - Russell, Tanya; Beebe, Nigel; Bugoro, Hugo; Apairamo, Allan; Collins, Frank; Cooper, Robert; Lobo, Neil; Burkot, Thomas
Abstract Background In the 1970s, Anopheles farauti in the Solomon Island responded to indoor residual spraying with DDT by increasingly feeding more outdoors and earlier in the evening. Although long-lasting insecticidal nets (LLINs) are now the primary malaria vector control intervention in the Solomon Islands, only a small proportion ofAn. farauti still seek blood meals indoors and late at night where they are vulnerable to being killed by contract with the insecticides in LLINs. The effectiveness of LLINs and indoor residual spraying (IRS) in controlling malaria transmission where the vectors are exophagic and early biting will depend on whether the predominant outdoor or early biting phenotypes are associated with a subpopulation of the vectors present. Methods Mark-release-recapture experiments were conducted in the Solomon Islands to determine if individualAn. farauti repeat the same behaviours over successive feeding cycles. The two behavioural phenotypes examined were those on which the WHO recommended malaria vector control strategies, LLINs and IRS, depend: indoor and late night biting. Results Evidence was found forAn. farauti being a single population regarding time (early evening or late night) and location (indoor or outdoor) of blood feeding. IndividualAn. farauti did not consistently repeat behavioural phenotypes expressed for blood feeding (e.g., while most mosquitoes that fed early and outdoors, and would repeat those behaviours, some fed late at night or indoors in the next feeding cycle). Conclusions The finding thatAn. farauti is a homogeneous population is significant, because during the multiple feeding cycles required to complete the extrinsic incubation period, many individual female anophelines will enter houses late at night and be exposed to the insecticides used in LLINs or IRS. This explains, in part, the control that LLINs and IRS have exerted against a predominantly outdoor feeding vector, such asAn. farauti . These findings may be relevant to many of the outdoor feeding vectors that dominate transmission in much of the malaria endemic world and justifies continued use of LLINs. However, the population-level tendency of mosquitoes to feed outdoors and early in the evening does require complementary interventions to accelerate malaria control towards elimination.